Assessments on the Conditions of Persons Who have the Legal Right to Caretaking - Iliescu, Alina-Elena (Acta Universitatis Danubius. Juridica, 2022)
The legal maintenance obligation is one of the "well established" institutions in family law, in addition to the vast regulation, it also enjoys a multitude of opinions formulated by the doctrine and the courts, national and not only. However, it cannot be ignored that certain aspects are not fully clarified: the criteria for determining the state of need of the creditor of the maintenance obligation, the delimitation between this and the state of strict necessity, the meaning of the phrase "continuing studies" by the child who has become an adult, the meaning of the notion of the creditor's assets from which he can support himself and, last but not least, the delimitation between the creditor's inability to support himself from his work and the existence of a state of need as a result of his fault. In our analysis, we started from the provisions of the current Civil Code, trying to suggest solutions for the issues raised, with the help of established doctrine and decisions and rulings from judicial practice, some even before the entry into force of the indicated normative act.